Cerdas Saja Tidak Cukup, suatu Kajian Kecerdasan Majemuk (Kecerdasan Qur’ani) Tentang Ulil Albab - Ismail (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The Qur'an discusses more comprehensive intelligence (syamil). perfect (kamil), and integral (mutakamil). The Qur'an is the Word of God, while the others are only human thoughts which are dominated by scular instincts. just being smart isn't enough, it takes a higher level than just being smart to achieve recognition of the greatness of God and submission to the Creator. This level can be called